Influence of Starter Cultures on the Accumulation of Histamine and Tyramine in Vacuum-Packaged Otlu (Herby) Cheese During Ripening - Ekici, K.; Tarakci, z.; Alemdar, S.; Alisarli, m. (Asian Journal of Chemistry, 2010)
Effect of cheese starters ( Lactococcus lactis ssp. lactis and Lactococcus lactis ssp. cremoris; CC), yoghurt starters (Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus; YC) and helveticus starter (Lactobacillus helveticus; HC) on histamine, tyramine contents and some microbiologic properties of Otlu (herby) cheese were investigated in this study. The moisture and salt contents of cheese were similar for difference cultures but pH of CC cheese was higher than those of other cultures at the beginning of the ripening. Histamine and tyramine contents of CC cheese, on the other hand, were lower than other cheese samples and increased significantly during ripening. Coliform counts were determined as under < 1 at the end of the storage period in all cheeses while Enterobactericeae counts were decreased approximately to a value of 1 cfu. Lactic acid bacteria, yeast and mould counts of helveticus culture cheeses at 60 days was lower than that of other (p < 0.05) samples. Results indicated that addition of the different starter cultures on Otlu cheeses had no significant (p > 0.05) effect on compositional (moisture, salt contents and pH value) and microbiolo-gical (total aerobic mesophilic bacteria, coliform and Enterobactericeae counts) properties when compared with the other cheese samples.